Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/access.2020.2980324
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Tip Clearance Measuring Method Based on AC Discharge

Abstract: A new measuring system for the engine tip clearance based on alternate current discharge is proposed in this article. Firstly, theoretical analysis and numerical simulation of the system, as well as the experiment of gas discharge are introduced to prove the feasibility of the method. Then a validation platform is built to study the effects of different probe materials and structures, as well as changes in temperature and humidity under atmospheric pressure on the system. Finally, the system calibration and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Existing BTC monitoring methods mainly include five kinds of methods: the discharge probe method [6,7], the optical fiber method [8][9][10][11][12], the capacitance method [13][14][15][16][17], the eddy current method [18][19][20][21] and the microwave method [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Existing BTC monitoring methods mainly include five kinds of methods: the discharge probe method [6,7], the optical fiber method [8][9][10][11][12], the capacitance method [13][14][15][16][17], the eddy current method [18][19][20][21] and the microwave method [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Blade tip clearance (BTC) measurement plays an important role in monitoring the condition and optimizing the performance of turbomachinery. BTC is defined as the radial distance between the rotor blade and casing, which has a great correlation with the efficiency and safety of turbomachinery [1][2][3][4]. Numerous studies have shown that too large a BTC will cause flow leakage and engine efficiency loss, whereas too small a BTC has the risk of friction collision between the rotor blade and casing because of blade load change, casing deformation and thermal expansion [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%